Analisis Kecurangan Laporan Keuangan Perusahaan: External Pressure, Financial Target, dan Financial Stability - Satiman, Satiman; Ramdani, Edon; Suparmin, Suparmin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine and analyze the influence of external pressure, financial targets, and financial stability on corporate financial statement fraud, both partially and simultaneously, in healthcare sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employs a quantitative approach to obtain objective and measurable results. The sample was selected using a purposive sampling technique, resulting in eight companies that met the established criteria during the observation period. The data used were obtained from the companies’ officially published annual financial statements. Analytical methods employed include descriptive statistical analysis, panel data regression model selection, classical assumption testing, and hypothesis testing. Data analysis was carried out using EViews 12 software to ensure statistical accuracy, robustness, and model reliability. The results of partial testing indicate that external pressure and financial targets have no significant effect on financial statement fraud, while financial stability has a significant and positive effect. Meanwhile, the results of simultaneous testing show that external pressure, financial targets, and financial stability collectively have a significant influence on corporate financial statement fraud. These findings emphasize the importance of maintaining financial stability as a crucial factor in preventing fraudulent reporting practices within healthcare sector companies and promoting sustainable corporate integrity.